Risk factors and knowledge of ebola virus disease among hunters in Kwara State, Nigeria (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Ebola virus disease (EVD) is a hemorrhagic, severe, often fatal, zoonotic disease transmitted by exposure to body fluids of infected bats and non-human primates. This study assessed the risk factors and knowledge of EVD among hunters in Kwara state. We conducted a cross-sectional survey of 427 hunters using a structured questionnaire that was administered between January and April 2016.      Most of the hunters (99.3 %, n=424/427)) were male and the mean age was 39 years. The mean knowledge score was 4.3±0.9. Most of the hunters (96.2%, n=411/427) were aware of EVD but only 42.6% (n=182/427) of them had good knowledge (GK) of the disease. About one-quarter (22.5%, n=96/427) of the hunters hunted bats and monkeys and 17.1% (n=73/427) of them have consumed raw or undercooked game animals (bush meat). The knowledge of EVD was significantly influenced by the marital status, form of education, occupation, and religion. Hunters who went through conventional western education (OR:4.6; 95% CI: 2.6, 8.1; p